Inventory of Plant Species with Potential as Botanical Pesticide in Bowi Subur Village, Masni District, Manokwari Regency: Inventarisasi Jenis Tumbuhan Berpotensi sebagai Pestisida Nabati di Desa Bowi Subur, Kecamatan Masni, Kabupaten Manokwari - Susim, Henok; Sadsoeitoeboen, Maria Justina; Lefaan, Paskalina Theresia; Sianipar, Fajar Ria Dwi Natalia; Maturbongs, Agatha Cecilia; Susanto, Slamet Arif (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
Using synthetic pesticides has polluted the environment, so efforts are needed to find alternative natural pesticides from plants. This study examines plant species with potential as botanical pesticides in Bowi Subur Village, Masni District, Manokwari Regency. The research method used is descriptive, with a sampling technique combining plot line transects, and it was conducted along 13 transects corresponding to the housing areas in Bowi Subur Village. The plants were documented, and relevant literature was reviewed. The inventory results identified 46 plant species from 25 families with pesticidal properties. Of these, 35 species are used for pest control, seven for disease management, and one for weed control. Additionally, three plant species were found to be effective for both pest and disease control. Most parts used for pesticide purposes are leaves, accounting for 19 plant species. We conclude that most species of plants used as natural pesticides are cultivated plants. Therefore, wild plants with potential for botanical pesticides are essential for further study their properties.